Clinical manifestations, laboratory findings, treatment and outcome of acute organophosphate or carbamate intoxication in 102 dogs: A retrospective study. (September 2019) - Klainbart, S.; Grabernik, M.; Kelmer, E.; Chai, O.; Cuneah, O.; Segev, G.; Aroch, I.
Highlights: Acute cholinergic crisis from organophosphate or carbamate intoxication has a fair prognosis. Most dogs showed classic cholinergic signs, however, only 17% showed all signs concurrently. Intoxicated dogs show numerous laboratory abnormalities. Gastric lavage or activated charcoal treatment were associated with survival. Treatment with either atropine-sulfate, mannitol, or mechanical ventilation, was associated with increased mortality. Abstract: Organophosphates (OP) and carbamates are commonly used insecticides and important intoxication sources of humans and animals. Nevertheless, large scale studies of these intoxications in dogs are unavailable. The medical records of dogs presented to a veterinary hospital were reviewed retrospectively. The study included 102 dogs definitely diagnosed with acute OP or carbamate intoxication. The most common presenting clinical signs included muscle tremor, hypersalivation, miosis, weakness, vomiting and diarrhea. Hypersalivation, muscle tremor and tachypnea were significantly ( P < 0.05) associated with survival to discharge; while weakness, mental dullness, anorexia, pale mucous membranes and paddling were significantly associated with death. Common laboratory abnormalities included decreased butyrylcholine esterase activity, acidemia, increased total plasma protein, leukocytosis, hypochloridemia, hyperbilirubinemia, increased creatinine and alanine transaminase (ALT), aspartate transaminase (AST) and creatine kinase activities, and prolonged activated partial thromboplastin time (aPTT). Compared to the survivors, the non-survivors showed significantly: higher frequencies of thrombocytopenia, hypocarbemia, prolonged prothrombin time (PT), hypernatremia, hyperkalemia, hypocholesterolemia, hypoproteinemia, hypertriglyceridemia, increased ALT activity and increased urea concentration; lower median concentrations of venous blood bicarbonate, serum chloride and total CO2 ; and higher medians of PT, serum total bilirubin and urea concentrations, and ALT and AST activities. Intoxicated dogs were commonly treated with diphenhydramine, atropine-sulfate, antibiotics, diazepam and pralidoxime, while some (19.2%) required general anesthesia and mechanical ventilation. The survival rate of dogs treated by gastric lavage was higher ( P = 0.041) compared to that of the remaining dogs. Development of respiratory failure and mechanical ventilation requirement were significantly associated ( P < 0.001) with death. The mortality rate was 17%.